Safe Limits of Contrast Media for Contrast-Induced Nephropathy: A Multicenter Prospective Cohort Study - Nie, Zhiqiang; Liu, Yong; Wang, Chao; Sun, Guoli; Chen, Guo; Lu, Zuxun (Frontiers in Medicine, 2021)
Background The safe level of contrast media volume (CV) is an important modifiable risk factor for contrast-induced nephropathy (CIN). The safe limit of CV remains unclear and is limited to single-center studies. Our objective was to determine the association between the ratio of contrast volume-to-glomerular filtration (CV/GFR) and CIN in patients undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI) Methods We assessed the association between CV/GFR and the risk of CIN in 4254 patients undergoing CAG or PCI from the year 2013 to 2016, enrolled in the REICIN (REduction of rIsk for Contrast-Induced Nephropathy), a prospective, multicenter, observational cohort study. CV/GFR was calculated at the five primary GFR equation. Results Sixty-nine (1.7%) patients with a median contrast volume-to- chronic kidney disease epidemiology collaboration (CV/CKD-EPI) ratio of 2.16 (1.30 -3.93) have suffered from CIN. The CV/CKD-EPI demonstrated the best performance of model fit, discrimination (area under curve = 0.736), calibration, reclassification, and equation conciseness (1 variable). The CV/CKD-EPI ≥1.78 was statistical significance associated with CIN (adjusted odds ratio, 4.64(2.84-7.56); P<0.001). Furthermore, similar results were found in the subgroup analyses. conclusions The CV/CKD-EPI showed the best performance in patients undergoing CAG or PCI. CV/CKD-EPI ≥1.78 could be a more reliable and convenient predictor of CIN. Intraprocedural preventive measures should include a priori calculation of CV/GFR to limit contrast volume.